2020
DOI: 10.3390/ijerph17155457
|View full text |Cite
|
Sign up to set email alerts
|

Source of Social Support and Caregiving Self-Efficacy on Caregiver Burden and Patient’s Quality of Life: A Path Analysis on Patients with Palliative Care Needs and Their Caregivers

Abstract: Few studies have explored the inter-relationships of sources of social support and caregiving self-efficacy with caregiver burden and patient’s quality of life among patients with palliative care needs and their caregivers. This study tested the associations of two sources of social support (family and friends) and the mediating role of caregiving self-efficacy on caregiver burden and patient’s quality of life. A convenience sample of 225 patient–caregiver dyads recruited between September 2016 and May 2017 fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
35
1
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 54 publications
8
35
1
13
Order By: Relevance
“…As hypothesized, significant correlations of the CSNAT item scores with those of the C-M-CSI and C-CGI-18 were confirmed in this study, supporting the scale’s construct validity. These findings are also consistent with published studies that measured the relationships of the same constructs among carers of palliative care patients [ 13 , 14 , 18 , 33 ]. Surprisingly, this study found that the CSNAT was not significantly associated with the SSQ-6, which was not in line with the study’s hypothesis.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As hypothesized, significant correlations of the CSNAT item scores with those of the C-M-CSI and C-CGI-18 were confirmed in this study, supporting the scale’s construct validity. These findings are also consistent with published studies that measured the relationships of the same constructs among carers of palliative care patients [ 13 , 14 , 18 , 33 ]. Surprisingly, this study found that the CSNAT was not significantly associated with the SSQ-6, which was not in line with the study’s hypothesis.…”
Section: Discussionsupporting
confidence: 92%
“…The availability of tangible, informational, and emotional support might be beneficial for meeting the support needs of carers [ 42 , 43 ]. A local study has also shown that the sources of social support are important in influencing the perceived burden and needs of carers of palliative care patients, with stronger family support decreasing caregiver burden and needs [ 33 ]. Future research is recommended to examine which types and sources of social support are associated with the support needs of carers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, deeply influenced by thousands of years of traditional Eastern cultural teachings such as Buddhism, Taoism and Confucianism, filial piety and harmony have become the most important family values for Chinese people. 43 Therefore, it is not difficult to find that in China, family members (mainly the spouse and children) are almost the core caregivers of patients, taking care of all the living, psychological care and disease management during the long disease cycle. 44,45 On the other hand, the values of "Acceptance of Destiny" seem to permeate the way Chinese patients and their caregivers view health.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, self-efficacy is tantamount to a sense of agency [ 15 ], and with respect to caregiving, self-efficacy refers to the expectancies that people have not only about their ability to competently support the patient but also their ability to execute of coping strategies, especially in relation to their tenacity in attempting overcoming setbacks and the duration of their commitment to achieve their goals. Thus, the role of self-efficacy in cancer management is crucial because expectations of caregiving efficacy are inversely related to psychological distress, physical functioning, stress, burden and burnout and positively related to benefits for the patient [ 8 , 17 ].…”
Section: Introductionmentioning
confidence: 99%